Type of Drain in Chronic Subdural Hematoma—A Systematic Review and Meta-Analysis - Greuter, Ladina; Hejrati, Nader; Soleman, Jehuda (Frontiers in Neurology, 2020)
Background: Chronic subdural hematoma (cSDH) is one of the most common neurosurgical diseases, while burr-hole drainage is the most frequently used surgical treatment. Strong evidence exists that subdural drain (SDD) placement reduces recurrence rates. However, the insertion of a subperiosteal drain (SPD) was shown to lead to similar recurrence rates and less complications than SDD. The aim of this study is to provide a systematic review of the literature and conduct a meta-analysis of studies comparing SPD with SDD after burr-hole drainage of cSDH. Methods: Pubmed and Embase databases were searched using a systematic search strategy to identify studies on drain location up to December 2019. Two independent researchers assessed the studies for inclusion and quality. Primary outcome measure was recurrence, while secondary outcome measures were drain misplacement, morbidity, mortality, and clinical outcome. Besides randomized controlled trials (RCT), we included non-randomized prospective cohort studies, as well as retrospective cohort studies. A fixed effects model was used if low heterogeneity (I2 < 50%) was present, otherwise a random effects model was used. Results: Following removal of duplicates, we screened 1109 articles of which 10 articles were included in our qualitative and quantitative analyses. One study was an RCT, three were non-randomized prospective cohort studies, and the remaining articles were retrospective cohort studies or subgroup analysis. In these 10 articles, 1,553 patients were treated with SPD and 1782 patients with SDD. Comparing the recurrence rate of cSDH a significant difference was found between SPD and SDD insertion (11.9 and 12.3%; RR 0.8, 95% CI 0.67–0.97, I2 = 0%, z = −2.27, p = 0.02). SPD had significantly lower rates of drain misplacement and parenchymal injuries (1.2 and 7.8%; RR 0.17, 95% CI 0.07–0.42, I2 = 0%, z = −3.4, p = 0.0001), as well as morbidity (6.4 and 8.2%; RR 0.65, 95% CI 0.5–0.84, I2 = 44.5%, z = −3.32, p =0.0009). Mortality rates (5.0 and 4.6%; RR 0.83, 95% CI 0.6–1.14, I2 = 0%, z = −1.2, p = 0.25) and favorable clinical outcome (89.6 and 88.9%; RR 1.1, 95% CI 0.89–1.24, I2 = 54.2%, t = 0.98, p = 0.40) were comparable in both groups. Conclusion: The insertion of SPD after burr-hole drainage of cSDH showed lower rates of recurrence, drain misplacements and parenchymal injuries, as well as overall morbidity, while clinical outcome and mortality were comparable to SDD. Therefore, the insertion of SPD after surgical drainage of cSDH should be encouraged.